2018
DOI: 10.1016/j.aott.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different electrotherapy methods and exercise therapy in shoulder impingement syndrome: A prospective randomized controlled trial

Abstract: ObjectiveThe aim of this study was to assess and compare the effects of different electrotherapy methods and exercise therapy on pain, function and quality of life in shoulder impingement syndrome.MethodsEighty-three patients (66 females, 17 males; mean age: 48.2 ± 7.33 years) with shoulder impingement syndrome were selected and 79 of them were randomly allocated into four groups. Group 1 (n = 19, mean age: 47.89 ± 7.12 years) was given hot pack and exercises, Group 2 (n = 20, mean age: 47.70 ± 6.51 years) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 33 publications
(47 reference statements)
0
32
0
2
Order By: Relevance
“…Thus, the primary dysmenorrhea is a health problem that deserves attention and seeks non-medicated ways of therapy, such as the use of physical therapy modalities, such as exercises, heat and transcutaneous electrical nerve stimulation of low frequency 18 . But, a widely used analgesic modality in the physiotherapeutic field is the currents of medium frequency, in the CIV stands out, with interesting results not only in cases of pain, but also with functional improvements and quality of life, when used in isolation [19][20][21][22] or associated to ultrasound 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the primary dysmenorrhea is a health problem that deserves attention and seeks non-medicated ways of therapy, such as the use of physical therapy modalities, such as exercises, heat and transcutaneous electrical nerve stimulation of low frequency 18 . But, a widely used analgesic modality in the physiotherapeutic field is the currents of medium frequency, in the CIV stands out, with interesting results not only in cases of pain, but also with functional improvements and quality of life, when used in isolation [19][20][21][22] or associated to ultrasound 23 .…”
Section: Resultsmentioning
confidence: 99%
“…The analyzed trials demonstrated major differences in treatment duration, IFC parameters (classical patterns vs. premodulated patterns), pain measure (VAS and NRS), and study population (shoulder pain, neck pain, acute disk, plantar fasciitis, and chronic LBP). Another important difference was evident regarding the type and number of cointerventions, which ranged from exercise 48,57 to exercise, modalities, and medications 11,61 . These differences might contribute to the observed insignificant results and raise caution when considering the results.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it has been demonstrated that the combination of IFT with shoulder exercises [55], ultrasound, thermotherapy, and stretching [56] is effective in the management of frozen shoulders. Likewise, the use of IFT alone has shown to be clinically effective to relieve pain during movement and to increase pain-free passive shoulder mobility in hemiplegic shoulder pain [57] and, when combined with exercise therapy, seems to improve pain, function, and quality of life in individuals with shoulder impingement syndrome [58]. In the latter study, the effect of combining IFT with exercise therapy was; however, similar to that of including ultrasound or transcutaneous electrical nerve stimulation instead, in the intervention protocol [58].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the use of IFT alone has shown to be clinically effective to relieve pain during movement and to increase pain-free passive shoulder mobility in hemiplegic shoulder pain [57] and, when combined with exercise therapy, seems to improve pain, function, and quality of life in individuals with shoulder impingement syndrome [58]. In the latter study, the effect of combining IFT with exercise therapy was; however, similar to that of including ultrasound or transcutaneous electrical nerve stimulation instead, in the intervention protocol [58]. Indeed, IFT seems to be a potential, although modest, effective supplement to other interventions to decrease pain, compared to control or placebo treatments, in musculoskeletal pain disorders [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation